Unpacking Impulsive Buying Behavior: The Role Of Tiktok And Store Atmosphere Among Gen Z At Minisopink Pvj Bandung - Arlinda; Mohamad Hadi Prasetyo (Journal Economic Excellence Ibnu Sina, 2025)
This study aims to analyze the influence of TikTok social media and store atmosphere on impulsive buying behavior among Generation Z at the Minisopink Store PVJ Mall Bandung. Impulsive buying is often triggered by emotional and external stimuli, and this phenomenon is often found among Gen Z, who are strongly influenced by social media content and store atmosphere. Although the implemented marketing strategy has followed consumer trends, its implementation is considered not optimal in utilizing the potential for impulsive buying. This study uses a quantitative approach with descriptive and verification methods to understand the influence of these two variables. The research sample was obtained through a questionnaire distributed to respondents who met specific criteria, namely having shopped at the Minisopink Store PVJ Mall Bandung, following the store's official TikTok account, and actively using TikTok social media. The distributed questionnaire measured the extent of the influence of TikTok social media and store atmosphere on impulsive buying behavior. The results show that TikTok social media has a positive and significant influence on impulsive buying among Gen Z. Engaging TikTok content, such as promotional videos and other creative content, can trigger emotions and encourage the desire to buy products impulsively. On the other hand, store atmosphere, including elements such as interior design, lighting, and music, also showed a positive influence on impulse buying behavior. However, the effect was not significant, indicating that the store atmosphere is not yet fully capable of creating a strong enough emotional appeal to encourage impulse buying. This finding indicates that Minisopink's digital marketing strategy through TikTok has not maximized the potential of features such as hashtags and interactive videos (stitch), which can further increase user engagement. Furthermore, store atmosphere elements such as music also need to be improved to create a more immersive and engaging shopping experience.